The Needs of Family Members of Patients with Traumatic Brain Injuries Admitted to the Critical Care Unit in a Tertiary Hospital - Kanchai, Janchai; Inta, Nonglak (Journal of Nurses Association of Thailand Northern Office, 2025)
This cross-sectional descriptive study aimed to explore the needs of family members of patients with traumatic brain injuries admitted to critical care units in a tertiary hospital. It is also aimed to compare the needs of family members of patients with mild, moderate, and severe traumatic brain injuries. Data were collected between February 2023 and January 2024. The samples included 205 purposively selected participants. They were either blood relatives, legal guardians, or close kin who served as primary caregivers of the patients who’s hospitalized in surgical trauma critical care unit, neurosurgical critical care unit, or neurosurgical intensive care unit for at least 24 hours. The research instruments included a general demographic questionnaire for traumatic brain injuries patients, a general demographic questionnaire for family members, and a needs assessment questionnaire specifically designed for family members. Data were analyzed using descriptive statistics and the Mann–Whitney U test. The findings revealed that family members had an overall need at a high level (x ˉ = 3.5, SD = 0.28). Specific dimensions of needs were also rated as high level, including informational needs (x ˉ = 3.7, SD = 0.26), psychosocial needs (x ˉ = 3.62, SD = 0.35), and spiritual needs (x ˉ = 3.43, SD = 0.49), while physical needs were rated at a moderate level (x ˉ = 3.25, SD = 0.55). Furthermore, no significant differences were observed between the needs of family members of mild and moderate to severe traumatic brain injuries patients (p>.05). The findings of this study support the development of a spiritual health care system to promote interpersonal healings among healthcare providers, patients, and families. Additionally, critical care nurses should provide accurate and timely information that aligns with the highest specific needs of patients’ family members.